USE OF INTERACTIVE TECHNOLOGIES IN UKRAINIAN LANGUAGE AND LITERATURE LESSONS (Innovative professional education, 2025)
The article considers the issue of introducing interactive technologies into the process of teaching Ukrainian language and literature. Their impact on increasing students’ motivation, developing critical thinking, creative abilities, and active participation in the educational process is analyzed. The main advantages of using interactive methods are outlined, including the use of multimedia presentations, online resources, educational platforms, interactive whiteboards, and gaming technologies. The authors emphasize the importance of digital tools in shaping a modern educational space that contributes to the effective assimilation of material, improving the quality of knowledge, and engaging students.
Keywords: interactive technologies, digital tools, student motivation, critical thinking, active learning, multimedia resources